'Truly being a New Zealander': ascriptive versus civic views of national identity. (2nd September 2017) - Humpage, Louise; Greaves, Lara
ABSTRACT: This article explores the relative strength of public support for ascriptive and civic aspects of national identity to assess the boundaries of 'inclusion' or 'exclusion' within New Zealand's national imaginary. Data from the International Social Survey Programme (ISSP) module on citizenship in 2015 provide a unique window into public understandings of what characteristics are associated with 'truly being a New Zealander' in the 21st century. Although New Zealanders have relatively inclusive attitudes overall, those with low education and those who sit on the political Right or vote New Zealand First were more likely to relate to ascriptive views, while female and Māori respondents were more likely to associate with civic notions of New Zealandness. Older respondents were more likely to associate with both ascriptive and civic views about truly being a New Zealander. The implications of such findings for social cohesion and belonging will be of interest to both policy-makers and national identity theorists.